Bardziej martwa czy bardziej znana – teksty prasowe związane ze śmiercią Anny Przybylskiej - Ivana Dobrotová; Michał Hanczakowski (Postscriptum Polonistyczne)
The article contains analyses of the several press publications that appeared in Polish tabloids after Anna Przybylska’s death in 2014. The analysed material proves that a death of a celebrity holds an importance for media mainly because of her/his previous presence in media and not because of the consolation function of a text itself. Such texts are deeply rooted in a tradition of funeral literature, yet they serve completely different purpose.